Ionic block copolymer doped reduced graphene oxide supports with ultra-fine Pd nanoparticles: strategic realization of ultra-accelerated nanocatalysis - Cho, Kie Yong; Yeom, Yong Sik; Seo, Heun Young; Kumar, Pradip; Lee, Albert S.; Baek, Kyung-Youl; Yoon, Ho Gyu (ROYAL SOC CHEMISTRY, 2015)
We synthesized an ultra-fine Pd nanocatalyst supported by ionic block copolymer doped reduced graphene oxide (Pd-PIBrGO) for ultra-accelerated nanocatalysis. This hybrid catalyst exhibited exceptionally advanced catalytic performance for the reduction of methylene blue using miniscule quantities of Pd-PIBrGO due to facilitated diffusion of reagents, resulting in full reduction within a few seconds and showing a 280-fold increase of the rate constant over Pd-rGO without ionic block copolymers.
Keywords: METAL-ORGANIC FRAMEWORKS; CORE-SHELL NANOPARTICLES; ONE-POT; NANOCRYSTALS; REDUCTION; CATALYSIS; CHARGE; ARCHITECTURES; STABILITY; DESIGN